The ABC Model: Clarifications and Elaborations - Khalil, James (Terrorism and political violence, 2022)
This article responds to Clark McCauley’s commentary on our Attitudes-Behaviors Corrective (ABC) Model of Violent Extremism, in which he contrasts our framework with his own two pyramids model (developed with Sophia Moskalenko). In particular, we focus on further distinguishing between the “core” and “optional extra” elements of our ABC model, elaborating on how our interpretation deals with individuals who seemingly become involved in violence in the interests of the group, “unpacking” the concept of ideology through our ABC lens, and providing recommendations on how to measure attitudes and behaviors in a context specific manner.